KONTRIBUSI RETRIBUSI PEMOTONGAN HEWAN DALAM UPACARA ADAT RAMBU SOLO TERHADAP PAD DI KABUPATEN TORAJA UTARA TAHUN 2021-2022 KONTRIBUSI RETRIBUSI PEMOTONGAN HEWAN DALAM UPACARA ADAT RAMBU SOLO TERHADAP PAD DI KABUPATEN TORAJA UTARA TAHUN 2021-2022 - Azaria Claresta; Ninuk Wijiningsih (Faculty of Law, Universitas Trisakti, 2025)
The animal slaughter levy is the highest contribution related to traditional ceremonies. The formulation of the problem is whether the procedure for collecting regional levies on the slaughter of animals in the Rambu Solo' ceremony in North Toraja district is in accordance with PERBUP TORUT No. 31 of 2021 and whether the regional levy on the slaughter of animals in the Rambu Solo' traditional ceremony in 2021-2022 contributes to PAD in North Toraja district. This research is a normative legal research, with an analytical descriptive nature. Using secondary data in the form of primary and secondary legal materials. The data was analyzed qualitatively with deductive conclusions. The conclusion is that the contribution of the Animal Slaughter Levy in the Rambu Solo' Traditional Ceremony to PAD in Toraja Regency has increased significantly based on 2021-2022. In 2021-2022, it shows an increase of 4.3% from 2021. Although there has been an increase in levy revenue, the levy results in 2021-2022 did not reach the target given by the government. The obstacle to this does not happen is due to the small location of slaughterhouses, slaughterhouse rates tend to be high, uneven socialization in the community, thick culture and inadequate law enforcement and regulations.